Highly Reliable Power Circuit Configuration with SiC Chopper Module for Hybrid Fuel Cell and Battery Power System for Urban Air Mobility (UAM) Applications - Moon-Seop Choi; Chong-Eun Kim (Energies)
This paper proposes a high-reliability power conversion system optimized for Urban Air Mobility (UAM) applications, which utilizes silicon carbide (SiC) chopper modules within a hybrid fuel cell and battery structure. The system features a redundant power configuration that employs both a main and an auxiliary battery to ensure continuous and stable power supply, even under emergency or fault conditions. By integrating SiC-based power converters, the proposed system achieves high efficiency, low switching losses, and enhanced thermal performance, which are crucial for the space- and weight-constrained environment of UAM platforms. Furthermore, a robust control strategy is implemented to enable smooth transitions between multiple power sources, maintaining operational stability and safety. System-level simulations were conducted using PowerSIM to validate the performance and reliability of the proposed architecture. The results demonstrate its effectiveness, making it a strong candidate for future UAM power systems requiring lightweight, efficient, and fault-tolerant power solutions.